Struktur Komunitas Ikan di Sungai Naborsahan Danau Toba Sumatera Utara - Putri Ananda Tarigan; Yunasfi Djayus; Ani Suryanti (AQUACOASTMARINE, 2013)
This research was conducted in Naborsahan River, North Sumatera in April-June 2013. It was aimed to know water quality in Naborsahan River, fish community structure and the relationship between community structure and physical and chemical factors of water. A survey method was conducted using Purpose Random Sampling in 4 stations. The obtained data were principal component Analysis (PCA) and analyzed descriptively.This research obtained 8 families, 9 genus, 10 species and 10745 individual fish. Highest relative abundance was fish species Bilih of 98.83%, while the lowest was goldfish and Sword Platy fish is 0.016%. Diversity index, fish uniformity index obtained,dominance index and index of similarity ranged from 0.08–0.73, 0.04-0.53, 0.59 - 0.98 and 50% - 89%, respectively. Temperature, current velocity, depth, brightness, pH, dissolved oxygen, biochemical oxygen demand, phosphate, nitrite, nitrate and turbidity varied between 22-25oC, 0.24-0.44 m/s, 0.62-0.79, 0.45-0.76, 6.75-7.9, 7.1-10.9 mg/l, 2.22-8.06 mg/l, 0.003-0.005 mg/l, 0.424-0.584 mg/l, 0.039-0.059 mg/l and 4.207-16.617 NTU, respectively. The results of PCA showed that temperature, depth, brightness, pH, DO and BOD5 are highly correlated with community structure. While flow, turbidity, nitrate, nitrite and phosphate are the lowest correlating factor of community structure.Keywords: Diversity, Fish, Water Quality, Naborsahan.